PKM Pelatihan Implementasi Kurikulum Merdeka Pada SMK - Amiruddin; Muhammad Hasim; Wirawan Setialaksana; Aminuddin; Nur Fadhilah Umar (Vokatek: Jurnal Pengabdian Masyarakat, 2023)
The Merdeka Curriculum Implementation Training was carried out at one of the Vocational High Schools (SMK) in the city of Makassar. The problem faced by this partner is a lack of knowledge related to the implementation or implementation of the Merdeka curriculum, considering that the partner is a school that has just implemented the Merdeka curriculum, especially related to the implementation of the Teaching Factory  in schools, the new partner will implement the Merdeka curriculum in 2023 (first year) so still lacking and needs strengthening from related parties. In this activity we provide training in implementing the Teaching Factory  to support the implementation of the Merdeka Curriculum in Vocational Schools. Starting from implementation strategies, improving facilities, building collaboration with industry and Teaching Factory  activities in learning.